Genus- and host-associated codon usage bias patterns in coronavirus spike genes - Jia Jun Chew; Chong Han Ng (PLoS ONE, 2026)
Codon usage bias (CUB) reflects the combined effects of mutational pressure and natural selection and provides insight into viral evolution and host adaptation. Although previous studies have examined CUB in individual coronaviruses or at the whole-genome level, systematic comparative analyses focusing on the spike (S) gene—an important determinant of viral evolution and host adaptation—across all four coronavirus genera including Alphacoronavirus, Betacoronavirus, Gammacoronavirus, and Deltacoronavirus , remain limited. In this study, we analyzed CUB in coronavirus spike genes across multiple genera and host groups. Codon usage indices, including codon adaptation index (CAI), effective number of codons (ENC), and GC content at the third synonymous codon position (GC3s), were evaluated alongside multivariate and clustering approaches, including correspondence analysis, hierarchical clustering, heatmap visualization, and ENC–GC3s analysis. Significant differences in CAI and ENC were observed among coronavirus genera, whereas GC3s showed no significant variation, indicating that codon usage patterns are structured primarily by phylogenetic relationships rather than nucleotide composition alone. Multivariate and clustering analyses further supported genus-level organization of codon usage profiles. In contrast, host-based comparisons showed that CAI varied significantly across host groups, while ENC and GC3s remained relatively stable, suggesting that host-associated translational selection influences codon preference without substantially altering overall codon bias strength. Heatmap analysis revealed enrichment of A/U-ending codons and underrepresentation of C/G-ending codons across coronavirus genomes, with consistent suppression of (cytosine-guanine dinucleotides) CpG-containing codons. ENC–GC3s analysis indicated that most genomes deviate from the expected neutral curve, suggesting that factors beyond mutational bias contribute to codon usage patterns. These findings indicate that codon usage bias in coronavirus spike genes is shaped by a combination of virus-intrinsic constraints and host-associated selective pressures, providing a gene-centric, cross-genera framework for understanding coronavirus evolution and host adaptation.